Utilization of an Odoo Enterprise-Based Enterprise Resource Planning Framework to Enhance the Achievement of Accounting Digitalization in the MSME Sector - Vicky Dzaky Cahaya Putra; Dian Lestari (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the utilization of an Odoo Enterprise-based Enterprise Resource Planning (ERP) framework in enhancing accounting digitalization within the Micro, Small, and Medium Enterprise (MSME) sector, particularly at Nyonyah Cake & Bakery. The research problem focuses on the continued use of manual financial recording systems based on Microsoft Excel, which resulted in reporting delays, risks of human error, low data integration, and limited access to real-time financial information. This study employed a qualitative approach using a descriptive method through observation, interviews, and documentation studies. The ERP implementation was carried out gradually over a two-month period using the Accounting, Sales, Purchase, and Inventory modules within Odoo Enterprise. The findings indicate that the implementation of the Odoo Enterprise-based ERP system significantly improved operational efficiency, accelerated financial recording and reporting processes, reduced data redundancy, and enhanced the accuracy and transparency of financial information. Furthermore, the system supported faster and more data-driven managerial decision-making through real-time information integration. This research also produced an adaptive and incremental ERP implementation model specifically designed to meet the operational needs of food-sector MSMEs.